Analisis Proses Impor Pakaian Bekas oleh Pedagang di Pasar Gedebage Bandung - Rifqi Agianto; Ranti Febrianti; Ricky Firmansyah (Universitas Budi Luhur, 2023)
The existence of used imported clothes has become a separate problem in every country. In Indonesia, imported used clothes are still in great demand by the public. This can be seen from the increasing number of used imported clothing sellers that can be found, one of which is in Bandung’s Gedebage market. In Indonesia itself the government has banned the activity of importing used clothing to be traded because it can endanger health. This relates to consumer rights, especially the right to consumer security and safety. This study aims to determine the process of importing used clothing by traders in the Bandung Gedebage market. This research method uses a descriptive data analysis method and the data collection process that we carry out is with a literature study, where the data obtained is the result of reading several scientific papers that are used as supporting data from this research. From the results of this study, it was concluded that: import of used clothing from traders in the Bandung Gedebage market through distributors or agents in Bandung. then the imported clothes obtained will be sold to consumers based on the type of clothing chosen by the trader. The obstacles that many distributors or traders experience are because imported clothes are illegal goods in Indonesia